Strategi Inovasi Pemasaran Produk pada UMKM Pisana di K - tandoko, jason; Vionisia Efelin Utama; Diondre Theodore; Abigail Wulung; Elia Ardyan (LPPM Stikosa - AWS, 2024)
The presence of micro, small and medium enterprises (MSMEs) has an important role in the Indonesian economy, making a significant contribution to increasing employment opportunities, overcoming poverty, and becoming a source of foreign exchange income. However, in the era of rapidly developing information technology, MSME competition is influenced by technological developments, especially social media as a popular marketing platform. Pisana, an MSME in South Sulawesi that focuses on the production of banana chips, faces challenges in marketing and using modern technology. This research aims to provide innovation in developing MSME marketing strategies, with a focus on the use of AI technology. Through implementation methods involving interviews, meetings at production houses, and assistance in Expo activities, this research provides a solution in the form of using AI technology such as